A spatiotemporal super-resolution algorithm for a hybrid stereo video system. Issue 3 (March 2016) - Ge, Jing; Liu, Ju; Yuan, Hui; Ge, Chuan; Zhang, Boyang
Abstract This paper presents a spatiotemporal super-resolution method to enhance both the spatial resolution and the frame rate in a hybrid stereo video system. In this system, a scene is captured by two cameras to form two videos, including a low spatial resolution with high-frame-rate video and a high spatial resolution with low-frame-rate video. For the low-spatial-resolution video, the low-resolution frames are spatially super-resolved by the high-resolution video via the stereo matching, the bilateral overlapped block motion estimation, and the adaptive overlapped block motion compensation algorithms, while for the low-frame-rate video, those missed frames are interpolated using the high-resolution frames obtained by fusing the disparity compensation and the motion compensation frame rate up-conversion. Experimental results demonstrate that the proposed mixed spatiotemporal super-resolution method has a more significant contribution to both the subjective and objective qualities than the pure spatial super-resolution or the frame rate up-conversion.